Psychological Characteristics of Child Sexual Violence Perpetrators: Systematic Literature Review - Munawaroh, Chusnul; Rahayu, Yusti Probowati (Universitas Negeri Surabaya, 2025)
Background: Sexual violence with child perpetrators is a complex phenomenon that has various backgrounds. Although children should be protected and guided in their growth and development, there are a number of factors that can trigger deviant behavior, such as sexual violence with children as perpetrators. Objective: How to know the psychological characteristics of sexual violence with children as perpetrators from foreign journals, then understanding the forms of sexual violence crimes is important to do so that it can be used as a lesson and various efforts are made to follow up on various cases. Method: The Systematic Literature Review method was chosen as the approach in writing this article, starting with identifying foreign journals, previous research, then filtering journals that are relevant to the topic, and analyzing the research findings and interpreting them, what are the characteristics of child perpetrators in several cases of sexual violence. Results: The characteristics of the child perpetrators of sexual violence, when viewed from a psychological perspective, are influenced by many interrelated and sustainable factors. Conclusion: The characteristics of this children are slightly different from those of adult perpetrators, due to hormonal and psychological instability in their developmental stages, and the perpetrators are also in situations that do not support healthy emotional and moral development.